Penerapan Virtual Private Network Dalam Akses File Server Di Kantor Kecamatan Air Dikit - Santoso, Feby; Khairil, Khairil; Supardi, Reno (LPPJPHKI Universitas Dehasen Bengkulu, 2025)
The implementation of Virtual Private Network for file server access at Air Dikit Sub-District Office can assist Air Dikit Sub-District Office in managing files sent by each village office, as well as simplify the process for village offices to send population reports and other documents to Air Dikit Sub-District Office via Virtual Private Network. File server access at Air Dikit Sub-District Office is built using a Samba server with the Linux Ubuntu Server 24.04.1 operating system. The server contains 7 shared folders corresponding to the names of each village office within Air Dikit Sub-District, and each Village Office is assigned 1 operator account used to access these shared folders. Additionally, there is a condition where a village office cannot access another village office's folder due to the authentication and verification process for operator accounts on each shared folder. Based on the testing conducted, the use of Hamachi VPN is limited to only 5 users who can connect, as the Hamachi version used is still the trial/free version.